Financial safety indicators and their role in improving the performance of the banking sector in Iraq - Hassan, Zahraa Hussein (Journal of Economic, Administrative and Legal Sciences, 2022)
The Central Bank of Iraq focused on achieving financial stability in its strategic plan, through the introduction of partial and total precautionary policies (safety indicators), which are among the tasks of the supervisory authorities for the importance and necessity of assessing and following up on systemic risks on an ongoing basis, and financial safety indicators aim to reduce risks To which the banking sector may be exposed to enhance its ability to withstand internal and external shocks, the research adopted the descriptive analytical approach to prove the hypothesis and objectives of the research to reach conclusions and recommendations. Systematic risks that it may be exposed to and improve its performance by strengthening its financial position, as the research aims to know the role and effectiveness of financial safety indicators in assessing the financial situation of the banking sector, through the application and analysis of its indicators that serve as an early warning indicator for financial crises in addition to maintaining the strength and safety of institutions finances from internal and external shocks.